2014
DOI: 10.1002/lpor.201400113
|View full text |Cite
|
Sign up to set email alerts
|

High‐efficiency single etch step apodized surface grating coupler using subwavelength structure

Abstract: Grating couplers are key elements enabling the coupling of light between planar waveguide circuits and optical fibers. In this work, it is demonstrated using simulations and experiments that a high coupling efficiency can be achieved for an arbitrary buried oxide thickness by judicious adjustment of the grating radiation angle. The coupler strength is engineered by subwavelength structure, allowing straightforward apodization and single etch step fabrication. The design has been implemented using Fourier-eigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 21 publications
(56 reference statements)
0
64
1
1
Order By: Relevance
“…Grating directionality is typically limited by the interference effect due to the reflection at the interface between the BOX layer and the silicon substrate. We have demonstrated that a modification of the coupling angle is an effective technique to achieve the constructive interference condition [16,18]. In Fig.…”
Section: Uniform Grating Couplers With High Directionalitymentioning
confidence: 89%
See 3 more Smart Citations
“…Grating directionality is typically limited by the interference effect due to the reflection at the interface between the BOX layer and the silicon substrate. We have demonstrated that a modification of the coupling angle is an effective technique to achieve the constructive interference condition [16,18]. In Fig.…”
Section: Uniform Grating Couplers With High Directionalitymentioning
confidence: 89%
“…This advantageous feature is afforded by utilization of the concept of subwavelength grating (SWG) refractive index engineering. The SWGs have successfully been used to locally engineer waveguide properties in integrated optical devices [16,18,19,25,[29][30][31][35][36][37]. Here, we implement an SWG structure in the direction perpendicular to the light propagation, as a periodic arrangement of high-index material (silicon) segments and rectangular holes etched in the waveguide core.…”
Section: Surface Grating Coupler Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of fiber tilt angle of illumination θ, is highly design and application specific. It is possible to have very high efficiency non-uniform couplers with both shallow [18] as well as deep angles of incidence [19]. It may be pointed out that, for non-uniform designs, the modulation of individual grating strength results in a higher effective grating index than uniform couplers.…”
Section: Mode Overlapmentioning
confidence: 99%